Visualization analysis of research hotspots in nursing of children with congenital heart disease at home and abroad based on CiteSpace (基于CiteSpace的国内外先心病患儿护理研究热点的可视化分析) - GUO Shuping (郭淑萍); FAN Jifan (范纪燕); ZHEN Donglian (郑栋莲); TIAN Xiaoyan (田晓燕); YIN Changqi (殷昌祺); LIU Fanfan (刘翻翻); WANG Xiaolan (王小兰) (Journal of International Translational Medicine Limited, 2023)
Objective Based on CiteSpace, the current status, hotspots and frontiers of nursing research on children with congenital heart disease(CHD) at home and abroad in the past 20 years were analyzed visually. Methods Using Web of Science and China National Knowledge Infrastructure (CNKI) core database as statistical sources, with "nurs*" OR "congenital heart disease" OR "Children" as search terms in English, with "congenital heart disease" or "congenital heart disease" and contains "child" or "care" in Chinese at the same time as the main search strategy, to supplement the retrieval strategy was complementary, retrieval on January 1, 2002 to December 31, 2021, included in the relevant literature. Literature metrology and visualization methods were adopted in the analysis from perspectives of age distribution, high frequency keywords and keyword co-occurrence analysis, and cluster timeline map and emergence map of keywords were performed. Results A total of 297 articles in CNKI database and 223 articles in Web of Science database were included, and the number of published articles showed a slow growth trend. The top three countries with most publications were the United States, Germany and Brazil. Foreign researches focused on birth defects, heart surgery, pediatric nursing and other aspects of children with CHD, while domestic researches focused on perioperative nursing of children with CHD. Conclusion There is a gap between the research hotspots of Chinese studies and foreign studies. Future research can learn from foreign literature, further refine and deepen the research content, and provides a new research perspective for researchers. (目的 基于CiteSpace对近20年国内外有关先心病患儿护理研究现状、热点和前沿进行可视化分析。方法 以Web of Science和中国知网(CNKI)核心数据库为统计源, 英文以"nurs*"OR"congenital heart disease" OR "Children "为检索词, 中文以"先天性心脏病"或"先心病"同时并含有"患儿"或"护理"为主要检索策略, 以补充检索策略为辅, 检索2002年1月1日-2021年12月31日收录的相关文献。采用文献计量法及可视化研究方法从研究年限分布、高频关键词及关键词共现进行分析, 绘制关键词聚类及突现图谱。结果 共纳入CNKI数据库文献297篇, Web of Science数据库文献223篇。发文量呈缓慢增长趋势, 居前 3 位的国家分别为美国、德国和巴西。国外围绕先天性心脏病患儿的研究热点多集中在出生缺陷、心脏手术、儿科护理等方面, 国内研究集中在先心病患儿围术期护理方面。结论 中文文献研究热点与外文文献研究热点存在一定差距, 未来研究可借鉴外文文献, 进一步将研究内容细化深入, 为研究者提供新的研究视角。)